Pregnancy Outcomes of Infertile Patients Presenting to Our Assisted Reproductive Technology Center - Hasan Ali Inal; Zeynep Ozturk Inal (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aimed to evaluate whether the demographic and stimulation characteristics, treatment results, and pregnancy outcomes of infertile couples who applied to our assisted reproductive technology center vary according to the calendar year.